THE INFLUENCE OF MOTIVATION, COMPENSATION AND WORK ETHIC ON EMPLOYEE PERFORMANCE IN PT. LAZADA LOGISTICS ID ALEXINDO BEKASI BRANCH HUBS - Arini Endrawati (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review that examines theinfluence of motivation, compensation and workethics on employee performance. This research wasconducted at PT PT. lazada logistics id alexindo bekasibranch hubs. This research will focus on solvingperformance problems for the company's employees.This research will use a quantitative approach whichwill then be tested using SPSS statistical tools to testthe feasibility of the data, the feasibility of the modeland hypotheses